Implementing a Multi-Objective Linear Fractional Inventory Model Using a Fuzzy Approach - Kumar, Naresh (Mathematical Statistician and Engineering Applications, 2023)
This paper presents a fuzzy programming model as a means of addressing multiple management objectives concurrently within the context of a linear fractional inventory system. The objective of this study is to present a developing model and illustrate how it can be implemented through the use of numerous numerical examples. In this work, the methodology is applied to a problem with two distinct objectives. The generated fuzzy model is then analysed using a linear programming format. For convenience, the researchers have assumed that the cycle period only consists of a single phase. The optimal modelling formulation takes into account both the total amount of available funds and the total amount of available storage space.